2003
DOI: 10.1152/jn.00915.2002
|View full text |Cite
|
Sign up to set email alerts
|

Millivolt-Scale DC Shifts in the Human Scalp EEG: Evidence for a Nonneuronal Generator

Abstract: . Slow shifts in the human scalp-recorded EEG, including those related to changes in brain CO 2 levels, have been generally assumed to result from changes in the level of tonic excitation of apical dendrites of cortical pyramidal neurons. We readdressed this issue using DC-EEG shifts elicited in healthy adult subjects by hypo-or hypercapnia. A 3-min period of hyperventilation resulted in a prompt negative shift with a rate of up to 10 V/s at the vertex (Cz) and an extremely steep dependence (up to 100 V/mmHg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
98
2
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 44 publications
11
98
2
6
Order By: Relevance
“…It has been shown that the negative DC shifts of SD can be detected with scalp DC‐EEG,33, 59 although important ambiguities remain and further research is needed to develop a reliable technique. In the case of abrupt ischemia, recordings might be particularly complicated by large BBB‐generated DC potentials due to p ti O 2 and p ti CO 2 changes 49, 50. Nonetheless, results presented here should have immediate relevance to the biological understanding of human brain death,60 which should at least require the occurrence of terminal SD in cerebral gray matter.…”
Section: Resultsmentioning
confidence: 90%
“…It has been shown that the negative DC shifts of SD can be detected with scalp DC‐EEG,33, 59 although important ambiguities remain and further research is needed to develop a reliable technique. In the case of abrupt ischemia, recordings might be particularly complicated by large BBB‐generated DC potentials due to p ti O 2 and p ti CO 2 changes 49, 50. Nonetheless, results presented here should have immediate relevance to the biological understanding of human brain death,60 which should at least require the occurrence of terminal SD in cerebral gray matter.…”
Section: Resultsmentioning
confidence: 90%
“…16 and this work) frequencies. So far, the lower frequencies have been largely ignored for technical reasons (14,15,19,26). The ISOs described in the present work have properties that are unprecedented in the human EEG literature: a very low frequency of 0.02-0.2 Hz and a slow apparent propagation over cortical hemispheres.…”
Section: Discussionmentioning
confidence: 86%
“…In the present study, we used direct current (DC)-coupled EEG scalp recordings (14)(15)(16) to demonstrate that ISOs are, in fact, a salient, large-scale feature of the human EEG. They were tightly associated with a cyclic modulation of fast EEG activity as well as discrete EEG events such as K complexes and interictal activity.…”
mentioning
confidence: 99%
“…We used custom-made Ag/AgCl electrodes placed on short-circuited skin; for details of the recording procedure, see Voipio et al (2003) and Vanhatalo et al (2004). Each subject participated in two 30 min sessions.…”
Section: Methodsmentioning
confidence: 99%